Lipid levels, atrial fibrillation and the impact of age: Results from the LIPIDOGRAM2015 study. (November 2020) - Harrison, Stephanie L.; Lane, Deirdre A.; Banach, Maciej; Mastej, Mirosław; Kasperczyk, Sławomir; Jóźwiak, Jacek J.; Lip, Gregory Y.H.; ,; Al-Shaer, B.; Andrusewicz, W.; Andrzejczuk-Rosa, M.; Anusz-Gaszewska, E.; et al.
Abstract: Background and aims: An inverse relationship between lipid levels and atrial fibrillation (AF) has been suggested, but whether the association is upheld for all age groups remains unclear. The aim of the study was to examine associations between lipid levels and AF by age groups in a nationwide study in Poland. Methods: Multivariate Poisson regression models were used to estimate prevalence ratios (PRs) for AF by lipid levels. Low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), total cholesterol (TC), non-HDL-C and LDL-C/HDL-C ratios were grouped into quartiles. Results: Of the 13, 724 participants, 5.2% (n = 708) had AF. People with AF were older with more comorbidities, but lower lipid levels (all p < 0.05). The prevalence of AF was inversely associated with LDL-C (Adjusted PR (95% Confidence Interval) highest versus lowest quartile: 0.60 (0.48, 0.75)), TC (0.61 (0.49, 0.75)) and non-HDL-C (0.63 (0.51, 0.78)). The prevalence of AF was inversely associated with HDL-C (0.58 (0.46, 0.74)), but this was not statistically significant for people aged 75 years and older. For the LDL-C/HDL-C ratio, the prevalence of AF was only inversely associated with higher levels for people aged 75 years and older (0.75 (0.61, 0.94)). There was no statistically significant difference in prevalence of AF by TG levels. Conclusions: The results suggest an inverse relationship between lipid levels and AF. The inverse association between higher HDL-C and AF was only significant for people aged <75 years, whereas the inverse association between higher LDL-C/HDL-C ratio and AF was only significant for people aged 75 years and older. Graphical abstract: Image 1 Highlights: Cholesterol levels inversely associate with prevalence of atrial fibrillation (AF). Inverse association between high-density lipoprotein cholesterol (HDL-C) and AF was only apparent for people aged <75 years. Inverse association between low-density lipoprotein cholesterol/HDL-C ratio AF was only apparent for people aged ≥75 years.